Nutrition Policy and Programs in Ghana : The Limitation of a Single Sector Approach - Ghartey, Adom Baisie (World Bank, Washington, DC, 2017)
Although Sub-Saharan Africa has some of the worst nutrition indicators in the world, nutrition remains a low priority on the policy agendas of many African governments. This despite the fact that proven interventions are known and available and that investment in them is considered a cost-effective strategy for poverty reduction. This case study is one in a series seeking to understand (1) what keeps African governments from committing fully to reducing malnutrition, and (2) what is required for full commitment. It documents how the Ghanaian government has addressed the issue of malnutrition since Independence, examines what political and institutional factors have prevented full commitment, and identifies what conditions have moved the nutrition agenda forward at different points in time. The primary objective of this study as well as the series as a whole is to help African governments, development partners, and nutrition and health practitioners identify, understand and address the political and institutional obstacles preventing sustainable progress in nutrition.